Traditional building shop business transformation - Satrio Probo Nindito; Sutrisno Sutrisno; Dessy Isfianadewi (Jurnal Mantik, 2024)
Mitra Buildmart building shop is a company that operates in the field of selling various kinds of tools and building materials. Currently, there are a total of 4 stores under the auspices of TB Mitra Buildmart. TB Mitra Buildmart includes 4 stores named Mitra Utama (as the main store), Mitra Binangun (small outlet), Mitra Rejo (small outlet), and Mitra Jaya Pakem (small outlet). The Covid-19 pandemic has also resulted in a very rapid digital revolution, which of course will have a negative impact on stores if they are unable to adapt to technological developments. Transformation of business and operational processes is carried out with the aim of increasing efficiency which is generally carried out using digital technology, namely in this case digital marketing and cloud computing. In order for the store to remain competitive, management decided to carry out business transformation in an effort to increase efficiency, effectiveness and customer satisfaction